Fraud Risk Management and Fraud Prevention Factors in the Local Government - Tarjo, Tarjo; Anggono, Alexander; Yuliana, Rita; Said, Jamaliah; Sakti, Eklamsia (Journal of Accounting Research, Organization and Economics, 2025)
Objective study aims to empirically examine the influence of religiosity, leadership ethics, and local wisdom on fraudulent financial statement prevention by implementing Fraud Risk Management in local governments throughout Madura, Indonesia.Design/Methodology The research method used in this study is a quantitative survey method. The dependent variable of this research is fraudulent financial statement prevention. The independent variables of this research are religiosity, leadership ethics, and local wisdom. At the same time, the mediating variable in this research is Fraud Risk Management. The sample of this research is 252 respondents to test this study's hypothesis using Structural Equation Modeling-Partial Least Square (SEM-PLS).Results Religiosity, leadership ethics, and local knowledge also significantly positively affect the application of Fraud Risk Management and its impact on fraudulent financial statement prevention. This study's main finding is that religiosity, leadership ethics, and local wisdom indirectly influence fraudulent financial statement prevention through Fraud Risk Management.Research limitations/implications Discuss the limitations and implications of the research This research contributes to improving the prevention system in local government. Furthermore, applying Fraud Risk Management can mitigate fraudulent financial statements in local government.Novelty/Originality This research presents the latest results from applying Fraud Risk Management to prevent fraud, which is rarely explored in the government sector. Apart from that, the research gap in the weak ethical values in implementing Fraud Risk Management can be answered by adding moderating variables such as religiosity, leadership ethics, and local wisdom. The addition of the moderation variable improves the level of originality of this journal. It provides solutions and updates in implementing Fraud Risk Management in the regional government sector.